Hypofractionated radiotherapy in nine dogs with unresectable solitary lung adenocarcinoma. Issue 4 (16th May 2019) - Kawabe, Mifumi; Kitajima, Yuka; Murakami, Mami; Iwasaki, Ryota; Goto, Sho; Sakai, Hiroki; Mori, Takashi
Abstract: Although lung lobectomy is the most common treatment option for dogs with solitary lung tumors, surgery often cannot be performed at the time of diagnosis. In this retrospective, case series study, we described the effects of hypofractionated radiotherapy for tumor mass reduction in nine dogs with solitary lung adenocarcinoma that were later considered for surgical resection, and we assessed the tolerability of the radiation protocol. Tumors were deemed unresectable by the attending veterinarian. The dose prescription was 7.0‐12.0 Gy/fraction in four to seven fractions, administered weekly for a total dose of 40‐50 Gy. Treatment planning prioritized normal tissue dose constraints. The median interval between the last radiotherapy session and maximum tumor size reduction was 56 (range: 26‐196) days, with six and three dogs exhibiting a partial response and stable disease, respectively. Although acute and late radiation‐induced toxicity to the skin and/or lungs developed in all nine dogs, it was self‐limiting or improved with short‐term anti‐inflammatory treatment. Tumor progression after initial size reduction was confirmed in three dogs at 62, 126, and 175 days, respectively, after the last radiotherapy session. Seven of the nine dogs underwent lobectomy a median of 68 days after radiotherapy when tumors were in partial response or stable disease or at the time of progression, and five received systemic chemotherapy concurrent with or after radiotherapy. These findings suggest that hypofractionated radiotherapy for canine solitary lung adenocarcinoma is useful when the tumor is large or when surgery cannot be performed immediately after diagnosis.